Merespons Dinamika Globalisasi Melalui Integrasi Manajemen Pendidikan dan Psikologi Pendidikan dalam Pembelajaran - Hanifah Zulfa -; Aep Tata Suryana (Idaarotul Ulum, 2025)
Globalization brings rapid changes and complex challenges to education, affecting educational policies, curricula, and learning practices. These changes require educational systems to be managed adaptively and oriented toward holistic student development. This article aims to examine the importance of integrating educational management and educational psychology in responding to the dynamics of globalization in learning. The research method employed is a literature study using a descriptive-analytical approach to relevant scholarly publications from the last ten years. The findings indicate that globalization significantly influences competency demands, learning methods, and the roles of educators and educational institutions. Educational management provides a systematic and innovative framework for organizing learning processes, while educational psychology offers a foundational understanding of students’ behavior, motivation, and emotional needs. The integration of these two approaches contributes to the creation of an inclusive, humane, and effective learning environment, thereby improving educational quality and preparing learners to face global challenges.